Ethiopian exegetical traditions and exegetical imagination viewed in the context of Byzantine Orthodoxy - Ježek, Václav (HTS teologiese studies, 2022)
The following article analysed the originality and creativity of Ethiopian Orthodox exegesis in a broader context of Byzantine and post-Byzantine Orthodox traditions. The originality of Ethiopian exegesis lies in its relative freedom from the conservative and traditionalist development of exegesis in other Eastern Orthodox contexts marked by the Graeco-Roman philosophical milieu. The Ethiopian exegetical tradition, being linked with traditional schooling, has managed to maintain a highly contextual and lively relationship with the community, with contemporary problems and issues and with other traditions, while maintaining a relationship with its own historical background. Analysing the Ethiopian traditions in comparativist contexts is important, but some important questions need to be further asked as to ‘how’ and ‘why’ is an interpretation being produced, what is its exegetical premise and how exegetical imagination functions.Contribution: The article‘s input and contribution is manifold. As we have seen, a greater emphasis on the role and potential of the Ethiopian traditional ecclesial schools would facilitate their future preservation and function in a rapidly changing world with differing but often linear and exclusive developments in education. Furthermore, as discussed and demonstrated in the article, Ethiopian theological exegesis has a unique potential to contribute especially to contemporary Orthodox theology, which often struggles to maintain a balance between tradition and contextual or contemporary theology. The article further showed in this context that analysing exegetical traditions must also move beyond mere comparativist analysis and must include a broader study of the indeterminate or ‘mystical’ nature of interpretation which is intimately linked with the unpredictable or indeterminate dynamics of the world around us. Or in other words, how the exegete understands his or her freedom in interpretation.